Patient‐reported outcomes with cemiplimab monotherapy for first‐line treatment of advanced non–small cell lung cancer with PD‐L1 of ≥50%: The EMPOWER‐Lung 1 study. Issue 1 (29th October 2022) - Gümüş, Mahmut; Chen, Chieh‐I; Ivanescu, Cristina; Kilickap, Saadettin; Bondarenko, Igor; Özgüroğlu, Mustafa; Gogishvili, Miranda; Turk, Haci M.; Cicin, Irfan; Harnett, James; Mastey, Vera; Naumann, Ulrike; et al.
Abstract: Background: In the EMPOWER‐Lung 1 trial (ClinicalTrials.gov, NCT03088540), cemiplimab conferred longer survival than platinum‐doublet chemotherapy for advanced non–small cell lung cancer (NSCLC) with programmed cell death‐ligand 1 (PD‐L1) ≥50%. Patient‐reported outcomes were evaluated among trial participants. Methods: Adults with NSCLC and Eastern Cooperative Oncology Group performance status 0 to 1 were randomly assigned cemiplimab 350 mg every 3 weeks or platinum‐doublet chemotherapy. At baseline and day 1 of each treatment cycle, patients were administered the European Organization for Research and Treatment of Cancer Quality of Life‐Core 30 (QLQ‐C30) and Lung Cancer Module (QLQ‐LC13) questionnaires. Mixed‐model repeated measures analysis estimated overall change from baseline for PD‐L1 ≥50% and intention‐to‐treat populations. Kaplan–Meier analysis estimated time to definitive deterioration. Results: In PD‐L1 ≥50% patients (cemiplimab, n = 283; chemotherapy, n = 280), baseline QLQ‐C30 and QLQ‐LC13 scores showed moderate‐to‐high functioning and low symptom burden. Change from baseline favored cemiplimab on global health status/quality of life (GHS/QOL), functioning, and most symptom scales. Risk of definitive deterioration across functioning scales was reduced versus chemotherapy; hazard ratios were 0.48 (95% CI, 0.32‐0.71) to 0.63 (95% CI, 0.41‐0.96). Cemiplimab showed lower risk of definitive deterioration for disease‐related (dyspnea, cough, pain in chest, pain in other body parts, fatigue) and treatment‐related symptoms (peripheral neuropathy, alopecia, nausea/vomiting, appetite loss, constipation, diarrhea) (nominal p < .05). Results were similar in the intention‐to‐treat population. Conclusions: Results support cemiplimab for first‐line therapy of advanced NSCLC from the patient's perspective. Improved survival is accompanied by improvements versus platinum‐doublet chemotherapy in GHS/QOL and functioning and reduction in symptom burden. Abstract : This analysis from a phase 3 clinical trial in patients with advanced non–small cell lung cancer showed that improved survival with cemiplimab was accompanied by significant benefits relative to chemotherapy in patient‐reported global health status/quality of life and functioning. Patients treated with cemiplimab also reported a reduction in symptom burden for key disease‐related symptoms and symptoms generally associated with chemotherapy.